The Effect of Electronic Word of Mouth on Buying Interest with Brand Image Mediation as Intervening Variables on Consumers of Scarlet Whitening Products in the Shopee Application - Nurul Lutfiyah Rahimah; Arif Kuswanto (Budapest International Research and Critics University, 2022)
Scarlett Whitening is a local beauty brand that focuses on selling on the internet. This product is able to beat international brands in body care, which is 57% of the most popular, and is included in the second position of the top local skincare brands most in demand in e-commerce in 2021. Many forms of electronic word of mouth are carried out by Scarlett Whitening, but have not made its position in the first rank that can be defeated by a local brand that has just gone viral at this time even though the characteristics of e-wom are sufficient enough to make consumers' buying interest number one. The need for identity to be top of mind and consumer confidence and able to compete, in this case is the brand image. The purpose of this study is to find out the effect of e-wom on buying interest through brand image as an intervening variable on consumers of Scarlett Whitening products in the Shopee application. This type of research is quantitative with descriptive analysis. The number of respondents used is 400 consumers who have bought Scarlett Whitening in the Shopee application. The sampling technique is non-probability sampling and Likert scale and data analysis using the partial least square software SmartPLS 3.2.9The result is that electronic word of mouth (X) has a positive and significant effect on Buying Interest (Y). Electronic word of mouth has a positive and significant influence on Brand Image (Z). Brand Image (Z) has a positive and significant influence on Purchase Interest (Y). Electronic word of mouth has a positive and significant influence on Buying Interest through Brand Image.